Opening doors - Newman, Diana S (Jossey-Bass, 2002)
Includes bibliographical references (p. 207-213) and index.; How changing demographics are changing philanthropy -- Understanding diverse giving patterns -- Embracing diversity and inclusiveness -- Building awareness and cultivating prospects -- Turning diverse prospects into donors -- Advancing donor investment through major gifts -- Encouraging gift planning and endowment building -- Achieving success through collaboration -- Realizing the potential of diverse donors.